Bingo Regulation and the Feminist Political Economy of Everyday Gambling: In Search of the Anti-Heroic. Issue 6 (1st November 2016) - Bedford, Kate
Abstract: This paper uses bingo—a lottery-style game particularly popular with older working-class women—to take forward feminist political economy debates about the everyday. It highlights consumption and regulation as key to research on everyday political economy, and aims to contribute to studies of gambling as a marker of the everyday within critical political economy. Rather than seeing gambling primarily in terms of vernacular risk-taking, however, it argues that gambling is also a pathway into exploring other, more self-effacing political economies—of entertainment, fundraising, sharing, and 'having a laugh'. Focusing on three key areas of regulatory dispute (over how to win bingo; who can participate; and what defines the game), the research suggests that players and workers are (re)enabling the diverse, plural nature of bingo as a political economic formulation—involving winning; entertainment; fundraising; care; flirting; and playful speculation—in the face of technological and legal processes aiming to standardize the game's meaning as commercial gambling.